A strategy to explore stable and metastable ordered phases of block copolymers - Xu, Weiquan; Jiang, Kai; Zhang, Pingwen; Shi, An-Chang (The journal of physical chemistry. B, 2013)
Block copolymers with their rich phase behavior and ordering transitions have become a paradigm for the study of structured soft materials. A major challenge in the study of the phase behavior of block copolymers is to obtain different stable and metastable phases of the system. A strategy to discover complex ordered phases of block copolymers within the self-consistent field theory framework is developed by a combination of fast algorithms and novel initialization procedures. This strategy allows the generation of a large number of candidate structures, which can then be used to construct phase diagrams. Application of the strategy is illustrated using ABC star triblock copolymers as an example. A large number of candidate structures, including many three-dimensionally ordered phases, of the system are obtained and categorized. A phase diagram is constructed for symmetrically interacting ABC star triblock copolymers.